x-3x-6=-x

Simple and best practice solution for x-3x-6=-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-3x-6=-x equation:


Simplifying
x + -3x + -6 = -1x

Reorder the terms:
-6 + x + -3x = -1x

Combine like terms: x + -3x = -2x
-6 + -2x = -1x

Solving
-6 + -2x = -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-6 + -2x + x = -1x + x

Combine like terms: -2x + x = -1x
-6 + -1x = -1x + x

Combine like terms: -1x + x = 0
-6 + -1x = 0

Add '6' to each side of the equation.
-6 + 6 + -1x = 0 + 6

Combine like terms: -6 + 6 = 0
0 + -1x = 0 + 6
-1x = 0 + 6

Combine like terms: 0 + 6 = 6
-1x = 6

Divide each side by '-1'.
x = -6

Simplifying
x = -6

See similar equations:

| 12a^3+39a^2-36a= | | x+8x-2=3x | | y=1.2x-3.8 | | 100-15=2.5h | | Z/3=5/3 | | 22=3x+4 | | 50x=3 | | -48=6(a) | | 300(x)=5x-120 | | 1/6(x-20)=20 | | 5c-15=2c+7 | | x-(5/6)=4x+(1/8) | | 10x+21(x-2)=113 | | 1/x+3/x+2+6/8x+4 | | 13=m/-5 | | 7m=12 | | 15+.25=20+.05 | | 8+3k=4k-3 | | 0.3x-0.3(3-x)=0.6 | | 2x+17+x+5=97 | | (9m-2n)(5m+8n)= | | m=12 | | 1/2a+1/a | | p(50)=5(50)-120 | | 6x+12=6x-12 | | 1+1/x^2-20/x^4=0 | | 4x^3+24x^2+74x+50=0 | | 18b-24b=-36 | | -39=q/9 | | 9-2j=8j-1 | | pi/2x=pi/220 | | 18g-12g=-30 |

Equations solver categories